2011
DOI: 10.3917/mav.043.0253
|View full text |Cite
|
Sign up to set email alerts
|

Le CV anonyme : les visions des DRH

Abstract: Résumé Le management de la diversité constitue un défi central des politiques et des pratiques de ressources humaines. En matière de recrutement, les enjeux et les risques sont particulièrement importants. Des comportements discriminatoires à l’embauche peuvent être intentionnels ou se produire par défaut de professionnalisme ou par méconnaissance. L’évaluation de l’impact des mesures visant à inscrire la non-discrimination, l’égalité de traitement et l’égalité des chances dans les politiques, les pratiques et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…A large‐scale French randomized experiment concluded that minority applicants (immigrants in the study) were harmed by anonymous applications because some negative signals (e.g., spelling errors) were not ignored by recruiters even when information such as a foreign name had been removed (Behaghel et al, ). Indeed, some recruiters are reluctant to use anonymous application forms because they believe that nonjob‐related information may be useful to assess applicants’ suitability (Yedder, Frimousse, & Peretti, ). Despite these limitations, some researchers still consider anonymous résumés more than a "seemingly good idea" (Marchal, , p. 108).…”
Section: The Anonymous Résumé From Recruiters’ Viewpoint: a Debated Smentioning
confidence: 99%
“…A large‐scale French randomized experiment concluded that minority applicants (immigrants in the study) were harmed by anonymous applications because some negative signals (e.g., spelling errors) were not ignored by recruiters even when information such as a foreign name had been removed (Behaghel et al, ). Indeed, some recruiters are reluctant to use anonymous application forms because they believe that nonjob‐related information may be useful to assess applicants’ suitability (Yedder, Frimousse, & Peretti, ). Despite these limitations, some researchers still consider anonymous résumés more than a "seemingly good idea" (Marchal, , p. 108).…”
Section: The Anonymous Résumé From Recruiters’ Viewpoint: a Debated Smentioning
confidence: 99%
“…Mais les moyens pour y faire face peinent à montrer leur efficacité. Les effets positifs du CV anonyme, un temps considéré comme l'antidote aux discriminations à l'embauche, ont ainsi été remis en cause par différentes recherches (Behaghel et al, 2011 ;Yedder et al ., 2011). Prenant le contre-pied de l'idée du CV anonyme de rendre invisibles toutes les caractéristiques potentiellement différenciatrices, le CV vidéo (CVV) a émergé récemment, fondé au contraire sur le principe de visibilité du candidat.…”
Section: Le CV Video : Le Nouveau Visage De La Lutte Contre Les Discrunclassified